2012
DOI: 10.1088/1748-9326/7/3/035401
|View full text |Cite
|
Sign up to set email alerts
|

Storage, patterns, and control of soil organic carbon and nitrogen in the northeastern margin of the Qinghai–Tibetan Plateau

Abstract: This study tested the hypothesis that soil organic carbon (SOC) and total nitrogen (TN) spatial distributions show clear relationships with soil properties and vegetation composition as well as climatic conditions. Further, this study aimed to find the corresponding controlling parameters of SOC and TN storage in high-altitude ecosystems. The study was based on soil, vegetation and climate data from 42 soil pits taken from 14 plots. The plots were investigated during the summers of 2009 and 2010 at the northea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
88
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 49 publications
18
88
1
1
Order By: Relevance
“…Previous studies have reported that soil C and N stocks in the upper soil layers were positively correlated with MAP and negatively correlated with MAT; these findings are similar to our observations along a large aridity gradient (Follett et al, 2012;He et al, 2014;Liu et al, 2012;Miller et al, 2004). The depletion of fine soil particles due to the intensified wind erosion with increasing aridity could further deplete C and nutrients in arid systems because these particles have disproportionately greater amounts of C and nutrients than larger particles (Yan et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported that soil C and N stocks in the upper soil layers were positively correlated with MAP and negatively correlated with MAT; these findings are similar to our observations along a large aridity gradient (Follett et al, 2012;He et al, 2014;Liu et al, 2012;Miller et al, 2004). The depletion of fine soil particles due to the intensified wind erosion with increasing aridity could further deplete C and nutrients in arid systems because these particles have disproportionately greater amounts of C and nutrients than larger particles (Yan et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…These correlations were already observed in Polish soils (Fotyma, 2007) but were assumed to be related to soil texture. The strong correlation between SOC and N (r = 0.94, P>0.05) has been observed previously (Bationo et al, 2007;Liu et al, 2012) and could be due to manure and N-fertilizer applied at different doses in each parcel (plot), therefore inducing a correlation between SOC and N because the N content in soil is almost entirely dependent on the organic matter content. Hh is related to the concentration of acidic hydroxyl groups on soil surfaces inducing the strong negative correlation between pH and Hh.…”
Section: Results Of Physical and Chemical Analysessupporting
confidence: 59%
“…Changes in aboveground and belowground components caused by vegetation succession from alpine swamp meadows to alpine meadows and steppes have indirectly or directly resulted in a loss of ecosystem carbon stock 36 . In addition, more than 90% of belowground biomass in alpine grasslands has been shown to be concentrated in the top 30 cm of soil 37 , and SOC is concentrated in topsoil and correlates well with BPC in this area 38 . For those reasons, ecosystem carbon above ground and below ground at a 0–50 cm depth range, like soil carbon in permafrost, were easily influenced by permafrost degradation.…”
Section: Introductionmentioning
confidence: 82%
“…SM and soil clay fraction were the controls for EC from the stepwise linear regression result (Table 2). Permafrost degradation patterns have direct and indirect impacts on SM conditions, and soil texture is a critical factor for water retention, e.g., sandy soils have low available water capacity and silty-clay substrates have a high potential to hold water 38 . With the decrease of SM, species composition was relatively stable and weeds had difficulty invading in alpine meadows with high coverage 13 ; thus, variations in SC and PC gradually decreased as permafrost stability declined (Fig.…”
Section: Discussionmentioning
confidence: 99%